If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6Z + 6Z + 3z = 180 Combine like terms: 6Z + 6Z = 12Z 12Z + 3z = 180 Solving 12Z + 3z = 180 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-3z' to each side of the equation. 12Z + 3z + -3z = 180 + -3z Combine like terms: 3z + -3z = 0 12Z + 0 = 180 + -3z 12Z = 180 + -3z Divide each side by '12'. Z = 15 + -0.25z Simplifying Z = 15 + -0.25z
| 30=4000y | | 5x^2-3c-2=0 | | 15-2w=21 | | 30=2000x | | -(3a^4-6b)-5(3a^4+b)= | | -12-4a=3a-12 | | 20=9000x | | 6(4x-3)=2(12x+2) | | 33=5+x+3x | | -6n+2(-5-12n)=-12n-10(1-12n) | | h=5(7.8)-16 | | 60-10a=5a-5 | | 33=5+x+3x+x | | -7b-9(b-12)=-4(3b-11) | | 5g-10g+32=-7 | | 20=9000x-5000y | | 10x-35+3x=5x-7 | | 6+10t-4=7t+26-3t | | -8(1+3n)+9n=-2(8n+3) | | 2(-x+-5)+(-x)=x+(-6) | | 9+3y=21 | | 7x+7x+4x=180 | | (6x-5)(5x+4)= | | 11z= | | -6(1-4x)=-3(11+x) | | 3x^2=240 | | 18=12-y | | -6y-y-3=39 | | 3(x+2)4=3/4 | | 1.5g=13.5 | | 2(p-12)=5(p+3) | | x-9x+4=60 |